Investigation of Intestinal Enzyme Activity and Effects of Non-starch Polysaccharide on it - Piryaei, Masoumeh; Motamedi, Anahita; Mehrabi Far, Atefeh (International Journal of Engineering and Technology, 2018)
Background and Purpose: Shigella is a human shigellosis and its lipopolysaccharide is identified by 4TLR. The 4TLR is a family of pseudo-TOLL receptors and many immune routes are triggered by stimulating these receptors. Many studies show increasing of 4TLR expression in Mesenchyme stem cells under the influence of lipopolysaccharide. The main objective of this study was to identify the appropriate lipopolysaccharide of Shigella strains by stimulating the immune system for vaccine studies. Materials and Methods: In this experimental study, the stem cell of human Mesenchymal derived from bone marrow was treated by three dilution of 0.1, 0.01, and 0.001 extract of Shigella strains (Flexneri, Dysentery and Sonnei) containing lipopolysaccharide. Then, the expression of 4TLR at RNA level was evaluated by RT-PCR and Q-PCR techniques. Cells treated with phosphate buffer saline were considered as control group. Findings: The expression of 4TLR was observed in all treatments groups except for treatment groups with relative concentration of 0.001 sonnei and dysentery as well as control group. Changes in 4TLR expression were dose-dependent on all treatment groups. The highest expression was related to the treatment with Shigella Flexneri extract and the smallest was related to Shigella sonnei. The use of pure lipopolysaccharide of Escherichia coli as a positive control showed that the lipopolysaccharide in Shigella extract is responsible for increasing the expression of 4TLR. Conclusion: given the increased expression of 4TLR by Shigella extract, this extract is recommended to increase the efficacy of the vaccine.
Keywords: Cell Extracts; Laboratory Conditions; Intrinsic Immunity; Lipopolysaccharide; Shigella.